Rancang Bangun Sistem Absensi Terintegrasi Mahasiswa Jurusan Manajemen Informatika Politeknik Negeri Fakfak - Mualo, Ardhyansyah; Basri, Hasan (Politeknik Negeri FakFak, 2024)
Different types of attendance systems are used in various settings such as schools and companies, namely web-based systems that can be used as a substitute for absenteeism. Another attendance system being developed is a QR Code based attendance system which requires user verification using RFID fingerprint or voice command. It is necessary to develop an attendance system that uses RFID sensors at universities as a technological adaptation.Currently, lecture attendance at the Fakfak State Polytechnic College, especially in the Informatics Management Department, still uses a manual attendance system, namely taking attendance of students using an attendance book every class hour. Running absenteeism creates a problem, namely that it is impractical. The impracticality of this system can be that it takes a lot of time to register students one by one, thereby cutting into course hours. Not to mention the phenomenon of leaving absences which usually takes advantage of lecturers' negligence to sign the absences of friends who are unable to come. You can also directly sign attendance from the first meeting to the last meeting. So the author conducted research on making student attendance tools that use RFID, and can monitor student attendance data by lecturers via a website. Based on these problems, an attendance system based on RFID (Radio Frequency Identification) using NodeMCU is expected to be able to solve these problems.